2008
DOI: 10.1017/s0022149x08996978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological evidence for the occurrence of Anisakis sp. A (Nematoda, Anisakidae) in the Blainville's beaked whale Mesoplodon densirostris

Abstract: Twenty-three adults (only one male) and two fourth-stage larvae of Anisakis, recovered from the stomach of a Blainville's beaked whale (Mesoplodon densirostris) stranded in Galicia (NW Spain), were studied morphologically and molecularly. The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and sequencing studies carried out on the ribosomal DNA spacers and on the cox2 mitochondrial gene confirm that these nematodes belong to the taxon Anisakis sp. A, which was previously detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…The ratio between esophagus and ventriculus length can be a distinguishing morphological character for differentiating A. simplex (s.s.) from A. pegreffi (Quiazon et al 2008), and our measurement data also overlapped with A. simplex (s.s.) in their studies. Morphological analyses have been used for anisakid nematode identification (Berland 1961;Grabda 1991;Iglesias et al 2008). However, identifications solely based on morphological differences lead to much controversy due to the limitation of taxonomically valuable characters (Mattiucci and Nascetti 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between esophagus and ventriculus length can be a distinguishing morphological character for differentiating A. simplex (s.s.) from A. pegreffi (Quiazon et al 2008), and our measurement data also overlapped with A. simplex (s.s.) in their studies. Morphological analyses have been used for anisakid nematode identification (Berland 1961;Grabda 1991;Iglesias et al 2008). However, identifications solely based on morphological differences lead to much controversy due to the limitation of taxonomically valuable characters (Mattiucci and Nascetti 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Host specificity does not allow C. multipapillatum individuals to reach maturity in dolphins. The record of larval A. simplex (s.s.) in the Gervais' beaked whale may also be an accidental infection because ziphiids are known to be specific for A. ziphidarum and A. nascettii (Paggi et al 1998;Pontes et al 2005;Iglesias et al 2008). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A by Pontes et al (2005). Iglesias et al (2008) detected the presence of some adult worms from Blainville's beaked whales stranded along the Atlantic coasts of Spain; however, the nominal designation of the species was not possible because of the lack of male specimens in their collection that were in suitable condition to be analyzed morphologically. Our Caribbean data further confirms that this taxon belonging to the genus Anisakis is a species genetically closely related to A. ziphidarum, one with host preference for beaked whales (Ziphiidae; Mattiucci and Nascetti 2008).…”
Section: Nematodamentioning
confidence: 99%
“…Gibson et al (1998) reported A. simplex from a Blainville's beaked whale stranded on the British coast. Recently, Iglesias et al (2008) demonstrated by using sequences analysis of the mtDNA cox2 that the taxon Anisakis sp. detected as preadults in beaked whales in Valentini et al (2006) corresponds to that documented in fish at larval stages from Madeira and reported as Anisakis sp.…”
Section: Nematodamentioning
confidence: 99%